2005
DOI: 10.1002/adfm.200500450
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐by‐Layer Fabrication and Characterization of Gold‐Nanoparticle/Myoglobin Nanocomposite Films

Abstract: Multilayer thin films of ∼ 7 nm diameter gold nanoparticles (GNPs) linked with horse heart myoglobin (Mb) are fabricated, for the first time, by layer‐by‐layer (LbL) assembly on glass slides, and silicon and plastic substrates. The GNP/Mb nanocomposite films show sharp surface plasmon resonance (SPR) absorption bands that are used to follow the LbL growth of the film and to determine the kinetics of GNP adsorption on the Mb‐modified surface. The GNP/Mb nanocomposite films are characterized using atomic force m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 43 publications
(86 reference statements)
5
62
1
1
Order By: Relevance
“…The absorption maxima of these bands (l max ) were fixed at a wavelength of 542 nm and did not change with the number of dipping cycles. Previous reports [21][22][23][24][25][26][27] have pointed out that in multilayer gold nanoparticles, strong interactions between neighboring dipolar particles can readily take place, which cause a red shift in l max with increasing number of dipping cycles and/or generate a new absorption band at a longer wavelength. In our case, however, no such features appear in the spectra, as shown in Figure 2, suggesting that the gold nanoparticles in films are spatially separated from each other, probably because of the long PLGA chains attached to the gold nanoparticles, and that the interparticle interactions are relatively weak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption maxima of these bands (l max ) were fixed at a wavelength of 542 nm and did not change with the number of dipping cycles. Previous reports [21][22][23][24][25][26][27] have pointed out that in multilayer gold nanoparticles, strong interactions between neighboring dipolar particles can readily take place, which cause a red shift in l max with increasing number of dipping cycles and/or generate a new absorption band at a longer wavelength. In our case, however, no such features appear in the spectra, as shown in Figure 2, suggesting that the gold nanoparticles in films are spatially separated from each other, probably because of the long PLGA chains attached to the gold nanoparticles, and that the interparticle interactions are relatively weak.…”
Section: Resultsmentioning
confidence: 99%
“…The LbL assembly takes advantage of the same attractive forces that form complexes but in a controlled manner that produces thin, conformal films that can coat a variety of surfaces and thus are a powerful method for fabricating multilayer gold nanoparticle films. [15][16][17][18][19][20][21][22][23][24][25][26][27] In spite of these many reports, to the best of our knowledge, well-controlled gold nanoparticle assemblies guided with a polypeptide network have not yet been reported. The aim of this article is to construct homogeneously well-ordered gold nanoparticle multilayers assisted with a b-sheet peptide template.…”
Section: Introductionmentioning
confidence: 99%
“…[20] In the presence of the electrostatic attraction between GNPs and Mb-modified MWCNTs, partially transparent and conductive CNT/GNP/Mb nanocomposite thin films can be formed on top of glass slide substrates from the mixed solution. Our previous work has demonstrated that the size of Mb molecules is sensitive to ambient humidity at room temperature (RT).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] We recently presented a myoglobin (Mb)-linked GNP multilayer film-based sensor with an LSPR sensitivity to humidity arising from induced changes in the interparticle spacing rather than changes in refractive index or adlayer thickness. [17] Since the electrical conductivity of the Mb-linked GNP multilayer film is too small to be easily measurable, [20] the sensor is not compatible with electrical signals. To enable the humidity sensor to operate with either an optical or an electrical signal, or both, optically transparent and electrically conductive thin films of CNT/GNP/Mb nanocomposite were fabricated on glass substrates by incorporating MWCNTs into an Mb-linked GNP network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation